miR-122 Exerts Inhibitory Effects on Osteoblast Proliferation/Differentiation in Osteoporosis by Activating the PCP4-Mediated JNK Pathway - Yi-Chen Meng; Tao Lin; Heng Jiang; Zheng Zhang; Lun Shu; Jia Yin; Xiao Ma; Ce Wang; Rui Gao; Xu-Hui Zhou (Elsevier, 2020)
Osteoporosis is characterized by the reduction of bone mineral density and deterioration of bone quality which leads to high risk of fractures. Some microRNAs (miRNAs) have been confirmed as potential modulators of osteoblast differentiation to maintain bone mass maintenance. We aimed to clarify whether miR-122 could regulate osteoblast differentiation in ovariectomized rats with osteoporosis. miR-122 was upregulated and Purkinje cell protein 4 (PCP4) was downregulated in ovariectomized rats. PCP4 was identified as a target of miR-122 by dual-luciferase reporter gene assay. We transfected isolated osteoblasts from ovariectomized rats with miR-122 mimic or inhibitor or PCP4 overexpression vectors. Proliferation and differentiation of osteoblasts were repressed by the overexpression of miR-122 but enhanced by overexpression of PCP4. miR-122 could induce the activation of the c-Jun NH2-terminal kinase (JNK) signaling pathway, while PCP4 blocked this pathway. Rescue experiments further demonstrated that the inhibiting effects of miR-122 on osteoblast differentiation could be compensated by activation of the PCP4 or inhibition of JNK signaling pathway. Collectively, our data imply that miR-122 inhibits osteoblast proliferation and differentiation in rats with osteoporosis, highlighting a novel therapeutic target for osteoporotic patients.